Adnexal torsion in children: The role of family practice physicians and paediatricians. Issue 1 (February 2016) - Al-Turki, Haifa A.
المخلص: أهداف البحث: يعد التواء المبائض من الحالات غير المألوفة التي تعرض ابتداء على أطباء الأطفال وأطباء الأسرة. يمكن إنقاذ المبيض في حال تم التشخيص مبكرا وبالتالي إنقاذ الخصوبة المستقبلية. وتهدف هذه الدراسة إلى تقييم الأعراض الأولية٬ وأسباب تأخر التشخيص٬ والمخرجات٬ وأساليب التشخيص المبكر الموصى بها لالتواء المبيض. طرق البحث: تمت دراسة استعادية للأطفال في سن ١٨ فما دون من يناير ٢٠٠٤م إلى ديسمبر ٢٠١٣م. شملت البيانات المتحصل عليها من السجلات الطبية العمر٬ والأعراض الأولية٬ والمعالجات السابقة لأعراض مشابهة٬ والتأخر في طلب العلاج٬ والتاريخ المرضي٬ والنتائج السريرية٬ والاختبارات التشخيصية المعمولة٬ والتشخيص والعلاج. النتائج: تم تجميع بيانات ١٥ مريضا٬ لكن توفرت السجلات الطبية لأحد عشر مريضا فقط من مرضى التواء المبيض للمراجعة الكاملة. كان متوسط العمر لمجموعة المرضى ٩٬٩ +/- ٣٬٥ عاما. كما كان ألم البطن الشكوى المقدمة لدى الجميع (١٠٠ ٪) بينما اشتكى ٨ مرضى (٧٢٬٧ ٪) من القيء. وكان متوسط مدة الأعراض ٣٩٬٧ +/- ٦٦ ساعة. عالج كل تخصص من بين أطباء الأطفال وأطباء الأسرة أربعة (٣٦٬٣٪) مرضى. كان متوسط مدة التأخر لعرض المريض في المستشفى ٥٢+/- ٦٨٬٧٨ ساعة٬ والتأخر في التشخيص والعلاج الجراحي بعد التنويم في المستشفى ٩٬١ +/- ٢٬٧ ساعة. اقتصرت الأدوات التشخيصية قبل العملية الجراحية على الأشعة الصوتية وأشعة تدفق الدم. وأظهر الاستكشاف الجراحي غرغرينة المبائض التي تم استئصالها بنجاح. الاستنتاجات: نعتقد بأن أطباء الأطفال وأطباء الأسرة هم أول من يقوم بالتقييم الأولي لمرضى التواء المبيض وبالتالي ينبغي أن يكون لديهم درجة عالية من التوقع لتلك الحالات. وينبغي عليهم طلب الأشعة الصوتية وأشعة تدفق الدم في مرحلة مبكرة من التشخيص وإحالة المريض إلى مراكز العلاج المتخصصة حيث يمكن للتدخل الجراحي المبكر إنقاذ المبيض والحفاظ على الخصوبة مستقبلا. Abstract: Objectives: Ovarian torsion (OT) is uncommon and is initially presented to paediatricians and family medicine physicians. The aim of this study is to assess the presentation, reasons for delayed diagnoses, outcomes, and recommended modalities for the early diagnosis of OT. Methods: A retrospective study was carried out in children ≤18 years old from January 2004 to December 2013. The data gathered from medical records included age, presenting symptoms, prior treatment for the same symptoms, delays in presentations, past medical history, clinical findings, diagnostic tests performed, diagnoses and treatments. Results: Although the data of 15 patients were collected, only 11 medical records of patients with adnexal torsion were available for complete review. The average age of the participants in this study was 9.9 ± 3.5 years. All patients complained of abdominal pain; whereas 8 (72.7%) patients presented with vomiting. The average duration of symptoms was 39.7 ± 66 h. Each discipline of general practitioners and paediatricians attended four (36.3%) children. The average delay of presentation to the hospital was 52 ± 68.78 h, and the average delay in diagnosis and final surgery after admission to the hospital was 9.1 ± 2.7 h. Ultrasound and Doppler imaging were the only diagnostic tools used for pre-operative diagnoses. Conclusions: We believe that paediatricians and general practitioners are the first line of physicians to initially assess patients with OT, and they should have a high index of suspicion while managing patients with OT. They should perform early ultrasound and Doppler and refer patients to tertiary care centres where early intervention could save the patients' ovaries and future fertility.